Quarterly Economic Commentary, Autumn 2011 - DURKAN, JOSEPH; DUFFY, DAVID (ESRI, 2011)
The situation in the international economy has deteriorated in recent months. The eurozone debt crisis has not been resolved, rather it has spread, and now two major economies, France and Italy, are pursuing restrictive policies to contain budget deficits, in tandem with contractionary policies in Spain, Greece, Portugal and Ireland. As a consequence, output in the eurozone economy will perform very poorly and may contract year?on?year and is certainly likely to contract from the end of 2011 to the end of 2012. This will have the effect of making it difficult for all eurozone countries to meet fiscal targets. This outcome will also hamper the restructuring of the UK economy and reduce its growth prospects. The US economy now seems to have recovered from the poor performance that began in the fourth quarter of 2011. Given this very unfavourable background the Irish economy is likely to experience very limited growth ? less than 1 per cent for GDP and a fall in GNP next year. Three months ago the possibility of building on an improved performance in 2011 made us reasonably optimistic about growth in the economy and growth in employment. The deterioration in the eurozone economy makes that unlikely now, though the fiscal targets set for next year are achievable. If the eurozone were an economy with a fiscal and monetary authority, the present situation would call for an expansionary fiscal policy and a looser monetary policy accompanied by a realistic level of restructuring of the banking system. In the absence of such a structure, coordinated action is the obvious approach, yet the structures are not there to achieve this and the ECB has resolutely set its stance against a much more activist approach. The present situation contains elements reminiscent of policy during the Great Depression, when a mounting crisis was confronted by an orthodoxy that resulted in great poverty that could have been avoided. Without decisive intervention the eurozone economies will be seriously constrained, will grow very poorly and make the resolution of the debt crisis more difficult. We now expect export growth and the level of investment to be less in 2012 than previously forecast. Total final demand will grow only by about 1.9 per cent and domestic demand will fall again. Employment will weaken further and we expect the labour force to decline as participation rates fall and people emigrate. The Troika targets are likely to be realised this year, though perhaps not to the extent we had hoped. For 2012 the targets are also likely to be realised, in spite of the deteriorating international situation.
PUBLISHED
Dublin
Keywords: fiscal targets; international economics; Investment; Household consumption; Public Finances